Ofatumumab capacity to deplete B cells from chronic lymphocytic leukaemia is affected by C4 complement exhaustion. (20th May 2015) - Tempescul, Adrian; Bagacean, Cristina; Riou, Catherine; Bendaoud, Boutahar; Hillion, Sophie; Debant, Marjolaine; Buors, Caroline; Berthou, Christian; Renaudineau, Yves
Abstract: The management of patients with chronic lymphocytic leukaemia (CLL) has improved with the utilisation of ofatumumab as a novel anti‐CD20 monoclonal antibody. However, as half of the patients fail to respond to the treatment, the aim of this study was to evaluate circulating CLL cell depletion and clinical response according to the context of complement activation and FcγRIIIA polymorphism in ten CLL patients with relapsed/refractory disease. At the end of the treatment, results indicated that circulating CD5 + CD19 + CLL cell depletion was major (<0.01 × 10 9 /L) in 4 of 10 patients, partial (>50% decrease) in 4 of 10 patients and ineffective for the two other patients. No clinical modifications were observed following ofatumumab introduction. Ofatumumab administration leads to a rapid and important exhaustion of complement C4 levels in patients with initial lymphocytosis. C4 exhaustion was accelerated in a non‐responder patient, and incomplete in two patients with partial circulating depletion. Moreover, delaying weekly to monthly ofatumumab injections improved CLL cell depletion in two patients. FcγRIIIA 158 polymorphism (FF n  =   6 and VF n  =   4) was not associated with major and/or partial circulating CLL cell depletion. In conclusion, ofatumumab induces an important C4 exhaustion that needs to be taken into account when treating CLL patients with ofatumumab.